2017
DOI: 10.1177/875697281704800408
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Critical Success Factors on Value for Money Viability Analysis in Public–Private Partnership Projects

Abstract: Governments are increasingly entering partnerships with the private sector through the public–private partnership (PPP) model for the development of public projects. Value for money analysis is used to assess the viability of these ventures. This research aims to investigate the contribution of the PPP critical success factors to value for money viability analysis. Relevant data were collected through a questionnaire to establish the PPP critical success factors and value for money success criteria. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…Theoretically, this study contributes to the following ways: first, our study enriches the literature studies of CSFs and VFM by examining governmental attitude as a mediating variable that needs to be highly considered in ensuring VFM in PPP-based WMPs. It provides the support that government's attitude is essential for the legalization and financial guarantees of PPP-based WMPs (Almarri and Boussabaine, 2017;Bing et al, 2005). Second, our study revealed that using PPP for waste management is not positively related, but it is highly significant for the achievement of VFM in Ghana.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 72%
See 3 more Smart Citations
“…Theoretically, this study contributes to the following ways: first, our study enriches the literature studies of CSFs and VFM by examining governmental attitude as a mediating variable that needs to be highly considered in ensuring VFM in PPP-based WMPs. It provides the support that government's attitude is essential for the legalization and financial guarantees of PPP-based WMPs (Almarri and Boussabaine, 2017;Bing et al, 2005). Second, our study revealed that using PPP for waste management is not positively related, but it is highly significant for the achievement of VFM in Ghana.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 72%
“…This explains why the government has to change its attitude toward the private sector to ensure the active participation and successful delivery of PPP projects because the stronger the private sector consortium, the more experience it brings to design and develops the most efficient and effective project. This factor was ranked first in previous studies (Almarri and Boussabaine, 2017;Li, 2003;Cheung et al, 2009). IJMPB 13,6 Fourth, our study points out that PPP-based waste management positively influences the CSF (governmental attitude) in Ghana.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 73%
See 2 more Smart Citations
“…Governments in response have sought to seek alternative means of financing the much needed infrastructure while ensuring that it fulfills its other numerous responsibilities to its citizens, hence the move towards PPPs. Therefore, it could be said that the most important reason till date for the adoption of the PPP strategy in both developed and developing countries was solely constraints on government revenue (Almarri, 2017).…”
Section: Why the Need For Adopting Ppp Methods Of Procurementmentioning
confidence: 99%